2019
DOI: 10.30845/ijbss.v10n1p9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Demographic Factors on Customers’ Mobile Banking Services Adoption in Nigeria

Abstract: Demographically, the study examines the factors that affect customers to adopt mobile banking services in Benin City. The study specially investigated age, occupation, educational level, gender and income of customers as powerful variables that affects the adoption of mobile banking services by customers in Benin City. The study population consists of all commercial bank individual customers in Benin City. The simple random sampling was employed in order to determine the sample size of six hundred from the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…Research has revealed that demographic characteristics of individuals can influence the use of Digital-Banking with particular importance on consumer income (Pikkarainen et al, 2004;Laforet & Li 2005;Mujinga et al, 2018;Abayomi et al, 2019). Katiyar and Badola (2018) in their study revealed also, that individuals' technological background could be a severe obstacle in online banking adoption.…”
Section: Review Of Literaturementioning
confidence: 94%
“…Research has revealed that demographic characteristics of individuals can influence the use of Digital-Banking with particular importance on consumer income (Pikkarainen et al, 2004;Laforet & Li 2005;Mujinga et al, 2018;Abayomi et al, 2019). Katiyar and Badola (2018) in their study revealed also, that individuals' technological background could be a severe obstacle in online banking adoption.…”
Section: Review Of Literaturementioning
confidence: 94%
“…Despite the increased smartphones users across the globe, utilization of moveable devices for pecuniary purposes was limited to elite and city customers in most African states, from which Nigeria is not exempted [19]. For instance, Nigeria as on September, 2019 has over 121 million GSM subscribers, yet the percentage of those using mobile device for pecuniary dealings is still beyond the banking sector expectation [12]. This may not be unconnected to customers' uncertainties about the new services platform as most people do not have faith on the service channels [17].…”
Section: Security and Privacy Issues Of Mobile Banking Appsmentioning
confidence: 99%
“…However, despite these benefits and many more as pointed out in prior studies e.g., see [9,10], its growth in most of the evolving nations is far less than what is seen in advanced nations [11]. Furthermore, little investigations were carried out in Nigeria, in connection to Internet and mobile banking [12,13]. However, Baptista [10] argued that the pace at which m-banking is progressing in Nigeria and other developing countries is disturbing compared to some Asian-Pacific nations and European states.…”
Section: Introductionmentioning
confidence: 97%
“…The analysis of the studies on the role of income in mobile adoption (Alalwan et al, 2015;Mutahar et al, 2018;Chawla and Joshi, 2017;Alalwan et al, 2018;Abayomi et al, 2019) reveals that there are three main theoretical gaps. First, little research has analysed the influence of income on technology adoption.…”
Section: The Role Of Income In Arab Females' Mobile Phones Usagementioning
confidence: 99%